The existence of the arbitral clause and the will of the parties - Noriega Linares, Carmen María (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The order object of this comment considers admissible, in a partial sense, the order issued by the Court of First Instance nº 32 of Barcelona, in which the existence or not of a submission to arbitration is argued. The court order pronounces positively in relation to the jurisdiction plea presented by the defendant, which alleges the existence of an arbitration clause inserted in the import contract signed between the plaintiff and the defendant. This clause stipulates that the contract will be interpreted in accordance with Slovenian Law and the arbitration will take place in Ljubljana, Republic of Slovenia. For its part, the plaintiff and appellant alleges that there was no clear intention of the parties to introduce this arbitration clause and that its placement in the contract was the result of a material error. It adds that if the arbitration clause is considered as inserted, it should be considered inoperative and ineffective due to its insurmountable gaps and irregularities.